1995
DOI: 10.2466/pms.1995.80.1.299
|View full text |Cite
|
Sign up to set email alerts
|

Protective Filters in the Prevention of Asthenopia at a Video Display Terminal

Abstract: In this work 25,064 employees were studied with the aim of investigating whether the video display terminal (VDT) equipped with filters reduces the incidence of asthenopia with reference to weekly time spent at a VDT and duration of work at a VDT. Analysis showed that the filters themselves do not reduce the occurrence of asthenopia consequent to various factors (refractive defects, time spent at a VDT, and monitors' characteristics).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Shantakumari et al and Ranasinghe et al found that the use of screen filters was associated with reduced digital eye strain. Conversely, Scullica et al found that screen filters did not reduce digital eye strain in their large population of subjects. Additionally, Reddy et al found that a radiation screen filter failed to reduce digital eye strain.…”
Section: Management Of Digital Eye Strainmentioning
confidence: 90%
See 1 more Smart Citation
“…Shantakumari et al and Ranasinghe et al found that the use of screen filters was associated with reduced digital eye strain. Conversely, Scullica et al found that screen filters did not reduce digital eye strain in their large population of subjects. Additionally, Reddy et al found that a radiation screen filter failed to reduce digital eye strain.…”
Section: Management Of Digital Eye Strainmentioning
confidence: 90%
“…Many authors propose breaks as a management strategy . However, Reddy et al found that breaks alone were not associated with reduced symptoms, whereas looking at far objects during breaks was.…”
Section: Management Of Digital Eye Strainmentioning
confidence: 99%
“…22, NO. Past studies with earlier displays and contrast enhancing filters did not demonstrate significant overall benefits of the filters (Ç akir et al 1977, 1979). More recently, Scullica et al (1995) compiled symptom information on 25 064 workers, 28% of whom used AR filters. They did not measure a relationship between symptoms and use of an AR screen.…”
Section: Introductionmentioning
confidence: 99%
“…Glare was found to increase the amount of time required to read relatively easy passages but decreased the amount of time to read relatively difficult passages. [62] For long it has been postulated that use of antiglare filters can help alleviate the symptoms as the ambient light passes through the glare filter two times (in and out) but the light emitted from the monitor passes through the filter only once. Conflicting reports on the intervention have been found.…”
mentioning
confidence: 99%